2020
DOI: 10.3389/fimmu.2020.534099
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-33 in Staphylococcus epidermidis-Induced Septicemia

Abstract: Interleukin (IL)-33 is a member of the IL-1 family, which plays an important role in inflammatory response. In this study, we evaluated the effect of IL-33 on septicemia and the underlying mechanisms by establishing a Staphylococcus epidermidis (S. epidermidis)-induced septicemic mouse model. The expression of IL-33, IL-1α, IL-1β, IL-6, IL-17A, IL-22, and PGE2 were measured by double antibody sandwich enzyme-linked immunosorbent assay, and bacterial colony formation in peripheral blood and kidneys were counted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Emerging evidence showed that sST2 injection inhibited LPS-induced IL-6 and NF-κB pathways, regulated the immune response of macrophages, followed by a reduced production of inflammatory factors, and decreased LPS-mediated mortality [26][27][28][29]. Furthermore, the study showed that the IL-33/ST2 axis played a critical role in regulating the homeostasis of Th17 cells, with sST2 administration leading to increased serum levels of IL-17A [30][31][32]. Therefore, whether sST2 treatment can ameliorate LPS/D-GalN-induced acute liver injury still requires further investigation.…”
Section: Introductionmentioning
confidence: 94%
“…Emerging evidence showed that sST2 injection inhibited LPS-induced IL-6 and NF-κB pathways, regulated the immune response of macrophages, followed by a reduced production of inflammatory factors, and decreased LPS-mediated mortality [26][27][28][29]. Furthermore, the study showed that the IL-33/ST2 axis played a critical role in regulating the homeostasis of Th17 cells, with sST2 administration leading to increased serum levels of IL-17A [30][31][32]. Therefore, whether sST2 treatment can ameliorate LPS/D-GalN-induced acute liver injury still requires further investigation.…”
Section: Introductionmentioning
confidence: 94%
“…1 With the widespread use of indwelling medical devices and implanted foreign bodies, S. epidermidis has become a significant threat to medical device associated infections (MDAI), including catheter-related bloodstream and surgical site infections, infective endocarditis, and so on. [2][3][4][5] Recently, several studies have reported that the distribution of S. epidermidis in human clinical samples were higher than infections caused by Staphylococcus aureus in Greece and India. 6 Antibiotics have been used as the most commonly used first-line treatment for S. epidermidis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sST2 levels may be correlated with the severity of sepsis, and the early identification of the cause of septic shock in patients [ 53 ]. These data suggest that ST2 treatment inhibits the mobilization of inflammatory monocytes in Staphylococcus epidermidis-induced sepsis [ 54 ]. Notably, high levels of IL-33 significantly aggravated tissue damage in the lungs, liver, and kidneys of mice.…”
Section: Introductionmentioning
confidence: 99%